Front Cover: XAS and EPR in Situ Observation of Ru(V) Oxo Intermediate in a Ru Water Oxidation Complex (ChemElectroChem 3/2022). Issue 3 (28th December 2021) - Levin, Natalia; Casadevall, Carla; Cutsail, George E.; Lloret‐Fillol, Julio; DeBeer, Serena; Rüdiger, Olaf
Abstract : The Front Cover shows a periodic table focused on the Ru element and the complementary X‐ray absorption spectroscopies and electron paramagnetic resonance obtained by in‐situ spectroelectrochemistry to confirm the participation of the Ru(V) oxo in the catalytic water oxidation by this Ru molecular catalyst. More information can be found in the Communication by N. Levin et al .